Psychosocial aspects experienced by international university students during the Covid-19 pandemic - Elcher Elias, Alanna (2026)
Objective: To analyze the psychosocial aspects experienced by international university students during the COVID-19 pandemic. Methods: An exploratory quantitative study was conducted in 2022 with 117 international students from the University for International Integration of the Afro-Brazilian Lusophony. Data were collected in person using a structured questionnaire based on the SRQ-20 and adapted to the pandemic context. Analyses were performed using IBM SPSS Statistics 21 with descriptive statistics and association tests (p<0.05). Results: High prevalence of anxiety (57.3%), sleep disturbances (60.7%), fear of infection (72.6%), and loneliness (62.3%) was identified. The pandemic affected the socioeconomic conditions of 80.3% of the participants and the academic performance of 79.5%. Additionally, 65.2% reported needing psychological support, but only 19.4% accessed such services. Conclusion: The pandemic intensified emotional, social, and economic vulnerabilities among international students, highlighting the need for institutional strategies to enhance psychosocial support, mental health promotion, and assistance networks.